1998
DOI: 10.1007/s11738-998-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Light and nitrate induction of nitrate reductase in kinetin-and gibberellic acid-treated mustard cotyledons

Abstract: Nitrate reductase activity in gibberellic acid and kinetin treated mustard (Brassicajuncea Coss. cv. T-59 'Varuna') seedlings, grown in the presence or absence of light and/or NO3 was investigated. While both light and NO3, alone could induce NR activity, their combination showed additive effects. Kinetin treatment significantly promoted both light-and NO3-induced NR activities, assayed by either in vivo or in vitro techniques, whereas, gibberellic acid was almost ineffective. In the absence of both light and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…The positive effect of GAs on NR activity is well known (Khan 1996, Premabatidevi 1998. A marked rise in the protein content (Table 1) of the treated leaves may well be a consequence of this GA 3 intensified NR activity (Saroop et al 1998). This postulation is further complemented by the positive correlation between the content of proteins and that of the enzyme (r = 0.905**).…”
mentioning
confidence: 94%
“…The positive effect of GAs on NR activity is well known (Khan 1996, Premabatidevi 1998. A marked rise in the protein content (Table 1) of the treated leaves may well be a consequence of this GA 3 intensified NR activity (Saroop et al 1998). This postulation is further complemented by the positive correlation between the content of proteins and that of the enzyme (r = 0.905**).…”
mentioning
confidence: 94%
“…This was confirmed by in vivo and in vitro techniques (Saroop et al 1998(Saroop et al , 1999. It was concluded that two independent NR fractions operate, with apparently identical properties but separate control mechanisms.…”
Section: Resultsmentioning
confidence: 64%
“…Two forms of NR were detected in mustard cotyledons and both the forms were affected by KiN treatment (Saroop et al 1998). In the present work, the differential effects of tungsten on the two forms of NR are reported.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, some reports indicate the involvement of cytokinins as possible mediators in the induction of NR expression by nitrate (Parkash 1972, Samuelson et al 1995), whereas others suggest that nitrate and cytokinins stimulate NR gene transcription independently (Kende et al 1971, Rao et al 1984, Schmerder and Borriss 1986, Solomonson and Barber 1990). Synergisms between cytokinins and light in the induction of NRA have also been proposed (Kohler et al 1980, Saroop et al 1998, Suty et al 1993). Therefore, the question is raised whether a link could be established between cytokinins and temperature in the control of NR expression and activity.…”
Section: Introductionmentioning
confidence: 99%